Hubungan Konsumsi Makanan Cepat Saji dan Aktivitas Fisik dengan Status Gizi pada Usia Remaja di SMA Negeri 1 Pajangan - Mucharomah, Ammelia; Fitriani, Rosmauli Jerimia (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Adolescence is a critical period for growth and development, influenced significantly by lifestyle choices. This study investigates the relationship between fast food consumption, physical activity, and nutritional status among adolescents at SMA Negeri 1 Pajangan. Using a cross-sectional design, the research involved 243 respondents selected through random sampling. Data collection methods included Food Frequency Questionnaires (FFQ), 24-hour Physical Activity Level (PAL) recall forms, and anthropometric measurements. The Spearman correlation test revealed no significant relationship between fast food consumption and nutritional status (p=0.468) or between physical activity and nutritional status (p=0.648). These findings highlight the complex factors influencing nutritional status beyond diet and exercise, suggesting the need for multifaceted approaches to address adolescent health. The study underscores the importance of balanced interventions incorporating dietary education and physical activity to improve adolescent nutritional outcomes.